The missed potential of CD4 and viral load testing to improve clinical outcomes for people living with HIV in lower-resource settings - Ehrenkranz, Peter D.; Baptiste, Solange L.; Bygrave, Helen; Ellman, Tom; Doi, Naoko; Grimsrud, Anna; Jahn, Andreas; Kalua, Thokozani; Nyirenda, Rose Kolola; Odo, Michael O.; Ondoa, Pascale; Vojnov, Lara; et al. (PLOS Medicine, 2019)
In a Policy Forum, Peter Ehrenkranz and colleagues discuss the contribution of CD4 and viral load testing to outcomes for people with HIV in low- and middle-income countries.